A simplified model approach for mass transfer of a complex liquid mixture during soil venting - Lee, SH; Yeom, IT; Ahn, KH; Khim, J (SELPER LTD, PUBLICATIONS DIV, 2000)
A simplified model approach for multi-component mass transfer of a complex liquid mixture in porous media was proposed and experimentally evaluated. The method includes grouping of individual components of a complex mixture based on its gas chromatographic (GC) profile and treating each group as a pseudo-single compound. Soil venting experiments were conducted using soil artificially contaminated with gasoline. It was found that the predicted concentrations of individual gasoline components in the effluent air by the simplified approach are almost identical to the values estimated from the method that considers all the components of gasoline as independent variables. In general, the model predictions for the removal of both total gasoline and individual compounds agree well with the experimental data. However, in the later phase of venting, the estimated concentrations were somewhat higher than the measured values. It was suggested that grouping different compounds in complex mixtures based on their GC profiles and treating the groups as pseudo-single compounds be a very useful tool, saving greatly the analytical and computational efforts without sacrificing accuracy of the model.